Assessment of the air pollution tax and emission concentration limits in the Czech Republic - Juřík, Richard (OECD Publishing, 2021)
This paper assesses the design of the air pollution tax in conjunction with a stringency analysis of the emission concentration limits in the Czech Republic. The analysis draws upon a detailed database containing environmental reporting by industrial stationary sources. The assessment of the emission concentration limits focuses on analysing the shift of the statutory limits between 2013 and 2017 and the corresponding real-life measured concentration on individual source basis. It provides an assessment of stringency of the air protection instrument and also of the vintage differentiation applied in the form of transitional schemes. The stringency analysis of the emission concentration limits stringency is related to the air pollution tax relief provision
Keywords: Environment; Taxation; Czech Republic